2002
DOI: 10.1055/s-2002-35961
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thymic Tissue as a Rare and Confusing Entity

Abstract: A 16-year-old girl with intrathyroidal ectopic thymic tissue, which was diagnosed incidentally after surgery for thyroid nodule, is reported to emphasise the possible clinical and surgical presentations of this rare entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…It has been reported that 6% of ectopic cervical thymus can cause dysphagia, dyspnea or stridor; however, to our knowledge no such symptoms have been reported in cases with IET [8]. There have been rare cases of thymoma, thymic carcinoma and lymphocyte-predominant lymphoma arising from the ectopic thymic tissue [10,22,23]. Ectopic thymus can also undergo thymic hyperplasia and may potentially play a role in myasthenia gravis [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 6% of ectopic cervical thymus can cause dysphagia, dyspnea or stridor; however, to our knowledge no such symptoms have been reported in cases with IET [8]. There have been rare cases of thymoma, thymic carcinoma and lymphocyte-predominant lymphoma arising from the ectopic thymic tissue [10,22,23]. Ectopic thymus can also undergo thymic hyperplasia and may potentially play a role in myasthenia gravis [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Thymus is derived from both ectoderm and endoderm of the third and often the fourth branchial clefts and pharyngeal pouches along with the thyroid and parathyroid glands (16,17). During the sixth week of gestation, the epithelium of the third pharyngeal pouch differentiates into the inferior parathyroid and the thymus; the epithelium of the elongated ventral parts of the third pair of pouches proliferates and forms cavities (17).…”
Section: Discussionmentioning
confidence: 99%
“…During the sixth week of gestation, the epithelium of the third pharyngeal pouch differentiates into the inferior parathyroid and the thymus; the epithelium of the elongated ventral parts of the third pair of pouches proliferates and forms cavities (17). The bilateral primordia of thymic tissue migrate to the median plane, form the definitive thymus which then descends into the superior mediastinum (16,17). Ectopic thymic tissue may be located along this pathway from the angle of mouth or base of the skull to the superior mediastinum (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations